Sabhāṣyaviṣṇusahasranāmaprārambhaḥ - Śaṅkarācārya ("Śrī Veṅkaṭeśvara" Sṭīm Yantrālaye, 1930)
Hymn to Viṣṇu, Hindu deity, from the Mahābhārata, enumerating his one thousand names; includes commentary of Śaṅkarācārya.